2019
DOI: 10.36941/mjss-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Herdsmen/Native Farmers’ Violence in Benue State and Food Security in Nigeria

Abstract: The herdsmen/farmers' violence in Benue State, Nigeria has constituted security challenges and could have contributed to food insecurity as more than 2000 lives were lost in Nigeria and over 170,000 were internally displaced in Benue state, a state tagged "food Basket of Nigeria". The paper among others examined the effects of the violence on food production in Benue State and Nigeria. It was descriptive study that adopted mixed method, using quantitative and qualitative approaches by relying on secondary data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Therefore, food crops production has been negatively affected. This report is in consonance with the study of Alao et al,(2019) which posited that over 170000 farmers where chased from their farm settlements and homes. The remaining 10% participants opine that shortage of food crop production may be caused by some other factors such as increasing human population without a corresponding improvement in agricultural activities.…”
Section: Synthesized Reportsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, food crops production has been negatively affected. This report is in consonance with the study of Alao et al,(2019) which posited that over 170000 farmers where chased from their farm settlements and homes. The remaining 10% participants opine that shortage of food crop production may be caused by some other factors such as increasing human population without a corresponding improvement in agricultural activities.…”
Section: Synthesized Reportsupporting
confidence: 87%
“…Table 3 clearly showed that the entire interviewees regretted the negative results from the violence and there is urgent task to stop it for peace, law and order, to permeate the country. The studies of (Alao et al,2019;Edward, 2022 ;Lawal et al, 2018 ;Akinkuolie, 2018) adumbrated on the economic, social and political implications of the violence ensuing between herdsmen and farmers in Nigeria.…”
Section: Synthesized Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…We purposely selected the state because agriculture is the major source of livelihood for over 70% of its 4.25 million population [30]. However, the prolonged incidence of farmer-herder conflict has made Benue a center of resource-based conflict in Nigeria [31]. We wished, therefore, to understand the connection of this conflict in the context of ongoing ALUC.…”
Section: Study Areamentioning
confidence: 99%
“…population [30]. However, the prolonged incidence of farmer-herder conflict has made Benue a center of resource-based conflict in Nigeria [31]. We wished, therefore, to understand the connection of this conflict in the context of ongoing ALUC.…”
Section: Study Areamentioning
confidence: 99%